Paparan Gas Karbon Monoksida (CO) pada Pedagang Sate: Tinjauan Literatur - Faisal Al Farosi (Lembaga Pengembangan Kinerja Dosen, 2025)
Exposure to carbon monoxide (CO) gas in satay traders, who work in an environment exposed to charcoal burning smoke, can cause various serious health impacts. CO is a colorless, odorless and tasteless poisonous gas, which can bind to hemoglobin in the blood and inhibit the supply of oxygen to body tissues, causing poisoning. This research aims to review and analyze various studies related to CO exposure in satay traders, with a focus on the health effects they cause and the factors that influence the level of exposure. Based on a review of existing literature, CO exposure to satay traders can cause respiratory problems, such as shortness of breath and throat irritation, as well as increase the risk of cardiovascular disease, especially in those exposed in the long term. Several factors that influence the level of CO exposure include ventilation of the trading place, duration of exposure, and the type and intensity of fire used in the charcoal burning process. Studies also show that satay traders who work in areas with limited ventilation or in closed rooms tend to have higher CO levels compared to those who work outdoors with better air circulation. Therefore, it is very important to develop policies or educational programs for satay traders regarding the risks of CO exposure and steps that can be taken to reduce such exposure, such as improving ventilation and using safer burning technologies. It is hoped that this review will provide deeper insight into the importance of protecting satay traders from CO exposure, as well as encouraging further research to develop effective mitigation strategies.